162k views
4 votes
Math 171

-5^2 times (3/5)^3

2 Answers

2 votes

(−52)((−35)3)

=−25(−35)3

=−25(−27/125)

=27/5

User PriyankaK
by
5.7k points
4 votes

Answer:


(-5)^2*((3)/(5))^3=(27)/(5)

Explanation:


(-5)^2*((3)/(5))^3

Using , property of exponents,


(ab)^x=a^x* b^x

=
(-1)^2*(5)^2*((3^3)/(5^3))

Using , property of exponents,


(a^x)/(a^y)=a^(x-y)

=
(5)^(2-3)*{3}^3

=
(5)^(-1)*{3}^3

Using , property of exponents,


a^(-x)=(1)/(a^x)

=
(3^3)/(5)

=
(3*3*3)/(5)

=
(27)/(5)

Thus,
(-5)^2*((3)/(5))^3=(27)/(5)


User Merthan Erdem
by
5.4k points